1999
DOI: 10.1016/s0550-3213(99)00434-4
|View full text |Cite
|
Sign up to set email alerts
|

Gluino condensate and magnetic monopoles in supersymmetric gluodynamics

Abstract: We examine supersymmetric SU(N) gauge theories on R 3 × S 1 with a circle of circumference β. These theories interpolate between four-dimensional N = 1 pure gauge theory for β = ∞ and three-dimensional N = 2 gauge theory for β = 0. The dominant field configurations of the R 3 × S 1 SU(N) theories in the semi-classical regime arise from N varieties of monopole. Periodic instanton configurations correspond to mixed configurations of N single monopoles of the N different types. We semi-classically evaluate the no… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

17
391
1
1

Year Published

1999
1999
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 212 publications
(410 citation statements)
references
References 55 publications
17
391
1
1
Order By: Relevance
“…The ratio, 56) seems to be more stable: it follows from phenomenological [5], variational [7,27] and lattice [21,36,37] studies. It means that the packing fraction, i.e.…”
Section: Instanton Ensemblementioning
confidence: 92%
See 1 more Smart Citation
“…The ratio, 56) seems to be more stable: it follows from phenomenological [5], variational [7,27] and lattice [21,36,37] studies. It means that the packing fraction, i.e.…”
Section: Instanton Ensemblementioning
confidence: 92%
“…An educated guess for the non-perturbative potential induced by dyons is therefore 8) to which the perturbative potential (3.5) must to be added. Let me note that in the supersymmetric theory there is a similar non-perturbative potential [56] (but in that case it is an exact result) and the perturbative potential is absent. The perturbative potential (3.5) has minima at φ = 0, 2πT corresponding to trivial holonomy P = ±1, while the non-perturbative potential (3.8) has the minimum just in the middle, at φ = πT corresponding to the non-trivial holonomy Tr P = 0, which is one of the requirements of confinement.…”
Section: Dyons and Calorons With Non-trivial Holonomymentioning
confidence: 98%
“…This is in contrast with the n f = 0 case, where the theory on S 1 L is equivalent to a finite temperature pure Yang-Mills theory, where the theory deconfines at sufficiently high temperature [23]. In the supersymmetric n f = 1 case the one-loop potential vanishes and the center-symmetric vacuum is stabilized due to non-perturbative corrections [26][27][28].…”
Section: (L)mentioning
confidence: 99%
“…Thus, for small y, the leading-order contribution to the vortex partition function is due to vortices with winding number vectors denoted by n A , A = 1, 2, 3: 28) and their corresponding anti-vortices. Note that the vortex with (n 1 , n 2 ) = (−1, −1) corresponds to the affine root α 3 = − α 1 − α 2 of the SU(3) algebra.…”
Section: Jhep04(2012)040mentioning
confidence: 99%
“…The first studies of gauge dynamics in non-thermal circle compactifications were performed in supersymmetric theories and yielded many interesting results [3][4][5]. 1 More recently, it was shown that non-thermal circle compactifications offer a calculable window into the dynamics of general nonsupersymmetric gauge theories as well [7][8][9].…”
Section: Introduction and Outlinementioning
confidence: 99%